2015
DOI: 10.1128/aem.04221-14
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium glutamicum Methionine Sulfoxide Reductase A Uses both Mycoredoxin and Thioredoxin for Regeneration and Oxidative Stress Resistance

Abstract: A erobic metabolism and oxidative stress lead to the production and accumulation of reactive oxygen species (ROS). ROS induce oxidative damage to macromolecules, such as proteins, lipids, and DNA, ultimately inducing cell death and disease. In proteins, oxidation modification occurs mainly at the sulfur-containing amino acids, such as cysteine (Cys) and methionine (Met) (1). Oxidation of methionine leads to the formation of the R and S diastereomers of methionine sulfoxide (MetO) and results in either conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Since MSH is a key nonenzymatic antioxidant that protects the cells from ROS damage by directly scavenging free radicals and by serving as a cofactor for antioxidant enzymes, we were prompted to investigate whether Ino‐1 plays a role in removing ROS under stress conditions (Si, Xu, et al., ; Si, Zhang, et al., ). The ROS levels in vivo were detected using DCFH‐DA, a membrane permeable dye which passively diffuses into cells (Si et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since MSH is a key nonenzymatic antioxidant that protects the cells from ROS damage by directly scavenging free radicals and by serving as a cofactor for antioxidant enzymes, we were prompted to investigate whether Ino‐1 plays a role in removing ROS under stress conditions (Si, Xu, et al., ; Si, Zhang, et al., ). The ROS levels in vivo were detected using DCFH‐DA, a membrane permeable dye which passively diffuses into cells (Si et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity assays for various stress conditions were investigated as previously described (Si, Xu, et al., ; Si, Zhang, et al., ). Overnight‐grown cultures of C. glutamicum (LB broth, 30°C) were diluted 100‐fold with LB medium and exposed to CHP (11 mM), MD (4 mM), H 2 O 2 (100 mM), CdCl 2 (300 μM), NiSO4 (6 mM), IAM (40 mM), MG (10 mM), and CDNB (70 mM) at 30°C with shaking for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we have shown that MsrA plays an important role in hostile conditions, and not only can it reduce MetO to Met via the thioredoxin/thioredoxin reductase (Trx/TrxR) reducing system, but also the mycoredoxin 1/mycothione reductase/mycothiol (Mrx1/ Mtr/MSH) system (Si et al, 2015b). The purpose of the present study was to investigate the function of MsrB and compare it with MsrA.…”
Section: Introductionmentioning
confidence: 93%
“…We have earlier reported that the msrA deletion mutant showed a significant sensitivity in a hostile environment (Si et al, 2015b). To test whether MsrB has the same effect as MsrA does, the sensitivity of wild-type, DmsrA mutant, the complementary strain DmsrA (pXMJ19-msrA), DmsrB and the complementary strain DmsrB (pXMJ19-msrB) to H 2 O 2 (80 mM), cumene hydroperoxide (CHP, 8 mM) and CdCl 2 (0.3 mM) were tested (Fig.…”
Section: Msrb Plays a Limited Role Under Oxidative Stresses Compared mentioning
confidence: 99%
See 1 more Smart Citation